Pemanfaatan Kegiatan Corporate Social Responsibility Difablepreneur Sebagai Media Untuk Membangun Reputasi Bisnis Pertamina - Shabrina Farahzatu Ghassania; Agus Naryoso (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2021)
ABSTRACT This research is based on the problem of the many unfavorable views of the people of Tawangsari village towards people with disabilities, where people with disabilities are still often underestimated by many people. Not only that, most families there consider people with disabilities to be a disgrace that must be hidden even from their families. PT. Pertamina TBBM Boyolali wants to turn the village under its guidance into an inclusive village, this can be supported through a Corporate Social Responsibility (CSR) activity with a special community empowerment program for people with disabilities called CSR Difablepreneur. The purpose of this study was to determine how the Difablepreneur program activities carried out by PT. Pertamina TBBM Boyolali through CSR, using qualitative research methods. This research refers to the constructivism paradigm with a case study approach. The data collection techniques used in this study were in-depth interviews, observation and literature study. And the theory used in this research is legitimacy theory by Gary O'Donovan, institutional theory, stakeholder theory, general system theory by Ludwig von Bertalanffy, and symbolic interaction theory by George Herbert Mead. Based on the results of this study, in carrying out the CSR Difablepreneur program activities there are 5 components in it, namely building human capital, strengthening economies, assessing social chesion, encouraging good governance, protecting the environment. Of the five components, Pertamina is able to generate a good reputation. This reputation is formed from the strong perceptions of stakeholders on company performance and performance. Thus providing opportunities for companies to be able to get positive recognition from the community. In addition, the CSR Difablepreneur activities can also influence public attitudes. Where it is built from information obtained through mass media or other communication channels. This information will build awareness that Pertamina has a high level of concern for the social and economic quality of local communities. A good attitude reduces the risk of the emergence of negative public opinion, suppresses the potential for protest, sabotage and even an attitude of public anti-terrorism, so that the company's goals are achieved.